2021
DOI: 10.1002/jca.21948
|View full text |Cite
|
Sign up to set email alerts
|

Source plasma deferral trends: A 3‐year analysis of 255 centers in the United States

Abstract: Background Plasma contains many important proteins of therapeutic interest including albumin, clotting factors, and antibodies. Source plasma (SP) is in great demand particularly due to a shortage of immunoglobulin. To better understand how to increase supply, we examined SP donor deferrals for the previous 3 years. Study design This is a description of donor deferrals at 255 plasma donation centers in the United States for April 1, 2017 to March 31, 2020. Results A total of 4 587 923 events were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Overall, the source plasma donor population tends to be younger in comparison to whole blood donors. 48 The data in this study validates CSL Plasma's donor age group expansion and the low proportions of older donors could perhaps suggest that older donors should be actively recruited when developing hyperimmune globulin products in the future. Hispanic, African American, and Native American ethnic groups comprised a considerable proportion of the CCP donors in this study compared with others.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Overall, the source plasma donor population tends to be younger in comparison to whole blood donors. 48 The data in this study validates CSL Plasma's donor age group expansion and the low proportions of older donors could perhaps suggest that older donors should be actively recruited when developing hyperimmune globulin products in the future. Hispanic, African American, and Native American ethnic groups comprised a considerable proportion of the CCP donors in this study compared with others.…”
Section: Discussionsupporting
confidence: 69%
“…Our study contains one of the largest CCP donor cohorts to date and may, therefore, present the best reflection of ethnic differences in anti‐SARS‐CoV‐2 antibody response in the United States between the dates studied. The results of this study are generalizable to the US population because of the diverse population that was studied, which is distinct from the whole blood donor population 48 . Of note, regional demographic data indicated that the most common location for donors was the Southwest.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although capturing the exact reason for the deferrals was not part of the survey, other publications showed that two of the most common reasons for deferral are unacceptable blood pressure and/or pulse and, for female donors, low hemoglobin/hematocrit. 14,16 Multiple studies have shown that these deferrals are also reasons for donors dropping out of whole blood donation. [17][18][19] For female donors, health-related concerns played a more significant role in deciding not to continue donations.…”
Section: Discussionmentioning
confidence: 99%
“…HP responses were reasons a participant attributed to the plasma donation, including issues with phlebotomy or veins, not feeling well after donating plasma, an unexpected reaction after donating plasma, or low or abnormal protein levels, or reasons that have an unknown relationship to plasmapheresis, including an unspecified concern about their health, being told by a health care provider to stop donating, or being deferred multiple times during the screening process. 14 HNP responses were reasons that could not be directly attributed to the donation process, including having a surgery, accident, injury, or illness, or for female donors, becoming pregnant. Personal responses included finding plasma donation painful, losing interest in plasma donation, experiencing poor customer service, the plasma center staff stating the donor could not donate again, donating plasma or blood elsewhere, getting a tattoo or, for male donors, having sex with another man.…”
Section: Methodsmentioning
confidence: 99%